Anti- Bullying Educational Strategy in an Effort Strengthen children’s Mental Health in MIN 1 Malang - Sakarina, Ainayya Nabila; Ishomuddin, Ishomuddin; Mukhlis, Fahrudin (Postgraduate Program Magister Pendidikan Agama Islam, 2024)
Bullying is currently increasingly widespread and worrying, Anti Bullying Education is one form of program that has been implemented by MIN 1 Malang City in providing important solutions that can be implemented not only with prevention, mental and emotional strengthening of students is also needed. Bullying problems can lead to fatal consequences. According to the Muslim philosopher by Ibn Sina, the human soul is the control center of the human body and mind, the mental role has a lot to do with the physical. if this situation is sustainable, then the child's mentality can decline which has an impact on the decline in the child's attitude and learning The purpose of this study is first, to determine the role of anti-bullying education in efforts to strengthen children's mentality at MIN 1 Malang City. Second, to determine the success of the anti-bullying education program at MIN 1 Malang City. The research method uses a qualitative approach with descriptive research. The results of this study are that it has a significant role in efforts to strengthen children's mentality, namely with spiritual education. Socialization that produces understanding, awareness or empathy and emotional management support by being a good listener and following up, social skills. and finally student independence. The success of anti-bullying education does not escape the support of all from a holistic approach, school community support, activities and socialization to parents, monitoring and evaluation.